Discovery of (R)-(3-fluoropyrrolidin-1-yl)(6-((5-(trifluoromethyl)pyridin-2-yl)oxy)quinolin-2-yl)methanone (ABBV-318) and analogs as small molecule Nav1.7/ Nav1.8 blockers for the treatment of pain. (1st June 2022) - Patel, Meena V.; Peltier, Hillary M.; Matulenko, Mark A.; Koenig, John R.; C. Scanio, Marc J.; Gum, Rebecca J.; El-Kouhen, Odile F.; Fricano, Meagan M.; Lundgaard, Greta L.; Neelands, Torben; Zhang, Xu-Feng; Zhan, Cenchen; et al.
Graphical abstract: Abstract: The voltage-gated sodium channel Nav 1.7 is an attractive target for the treatment of pain based on the high level of target validation with genetic evidence linking Nav 1.7 to pain in humans. Our effort to identify selective, CNS-penetrant Nav 1.7 blockers with oral activity, improved selectivity, good drug-like properties, and safety led to the discovery of 2-substituted quinolines and quinolones as potent small molecule Nav 1.7 blockers. The design of these molecules focused on maintaining potency at Nav 1.7, improving selectivity over the hERG channel, and overcoming phospholipidosis observed with the initial leads. The structure-activity relationship (SAR) studies leading to the discovery of ( R )-(3-fluoropyrrolidin-1-yl)(6-((5-(trifluoromethyl)pyridin-2-yl)oxy)quinolin-2-yl)methanone (ABBV-318) are described herein. ABBV-318 displayed robust in vivo efficacy in both inflammatory and neuropathic rodent models of pain. ABBV-318 also inhibited Nav 1.8, another sodium channel isoform that is an active target for the development of new pain treatments.